Past and current components-based detailing of particle image velocimetry: A comprehensive review - Rohacs, Daniel; Yasar, Onur; Kale, Utku; Ekici, Selcuk; Yalcin, Enver; Midilli, Adnan; Karakoc, T. Hikmet (CELL PRESS, 2023)
Particle image velocimetry has been widely used in various sectors from the automotive to aviation, research, and development, energy, medical, turbines, reactors, electronics, education, refrigeration for flow characterization and investigation. In this study, articles examined in open literature containing the particle image velocimetry techniques are reviewed in terms of components, lasers, cameras, lenses, tracers, computers, synchronizers, and seeders. The results of the evaluation are categorized and explained within the tables and figures. It is anticipated that this paper will be a starting point for researchers willing to study in this area and industrial companies willing to include PIV experimenting in their portfolios. In addition, the study shows in detail the advantages and disadvantages of past and current technologies, which technologies in existing PIV laboratories can be renewed, and which components are used in the PIV laboratories to be installed.
Keywords: Particle image velocimetry (PIV); Flow measurement; Component; Non-intrusive; Review; Aviation; UNSTEADY-FLOW STRUCTURE; TUBE HEAT-EXCHANGER; X-RAY PIV; TRACKING VELOCIMETRY; OPTICAL-FLOW; VELOCITY-FIELD; NATURAL-CONVECTION; TRACER PARTICLES; FLUID-DYNAMICS; REACTANT FLOW; Science & Technology - Other Topics